2016
DOI: 10.1186/s40536-016-0027-1
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of country differences in effects of parental education on children’s academic achievement

Abstract: Background: In a previous study, the total, direct and indirect effects of parental education on reading, mathematics and science achievement have been estimated for Grade 4 pupils of 37 countries that participated in PIRLS and TIMSS 2011 studies (Gustafsson et al. in TIMSS and PIRLS 2011: Relationships among reading, mathematics, and science achievement at the fourth grade-implications for early learning. pp 2013). Several theories proposed to account for the variation were reviewed. With this previous stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 25 publications
(25 reference statements)
0
4
0
Order By: Relevance
“…This is because parental education is commonly used in secondary analyses of ILSA (e.g. Martins & Veiga, 2010; Yang‐Hansen & Gustafsson, 2016)—as well as the social stratification literature more generally. The data we have available is also particularly well suited to studying this socio‐economic indicator.…”
Section: Methodsmentioning
confidence: 99%
“…This is because parental education is commonly used in secondary analyses of ILSA (e.g. Martins & Veiga, 2010; Yang‐Hansen & Gustafsson, 2016)—as well as the social stratification literature more generally. The data we have available is also particularly well suited to studying this socio‐economic indicator.…”
Section: Methodsmentioning
confidence: 99%
“…Parental involvement has been acknowledged as an important predictor of children’s academic success and researchers around the world have identified many factors that challenge parental involvement in children’s learning (Jeynes, 2011 ). Research has shown positive correlation between parental education/income status and student achievement (Idris et al, 2020 ) and according to Hansen and Gustafsson ( 2016 ), it can be explained “by the relations which go from parental education via the resources and different activities in the home to achievement…” (p. 5). Hansen and Gustafsson’s ( 2016 ) multi-country comparative study with 37 nations reported that the correlation between parent education and student achievement was higher for countries with higher income inequality because “education is more equitable in countries with less economic inequity” (p. 11).…”
Section: Parental Involvement In Remote Instructionmentioning
confidence: 99%
“…Research has shown positive correlation between parental education/income status and student achievement (Idris et al, 2020 ) and according to Hansen and Gustafsson ( 2016 ), it can be explained “by the relations which go from parental education via the resources and different activities in the home to achievement…” (p. 5). Hansen and Gustafsson’s ( 2016 ) multi-country comparative study with 37 nations reported that the correlation between parent education and student achievement was higher for countries with higher income inequality because “education is more equitable in countries with less economic inequity” (p. 11). To add, the school’s language of instruction also limits the involvement of parents who do not speak that language (Vera et al, 2012 ).…”
Section: Parental Involvement In Remote Instructionmentioning
confidence: 99%
“…the National Assessment of Educational Progress (NAEP). Also, numerous scholars have also investigated the gender gap and inequality of opportunity in education through secondary analysis and meta-analysis (Baye and Monseur 2016;Hansen and Gustafsson 2016) using large-scale assessment data. Moreover, the relationship between educational outcomes and other predictors, e.g.…”
Section: Introductionmentioning
confidence: 99%